Entre apeiron présocratique et métastabilité thermodynamique : l’idée de préindividuel chez Gilbert Simondon - Sarah Margairaz (Methodos, 2013)
The concept of ‘preindividual’ constitutes a lexical innovation in metaphysics, refering to a new idea by which Gilbert Simondon tries to depart from the traditionnal thinking of individuation. However, Simondon refers on several occasions to the presocratic notions of ‘apeiron’ and ‘phusis’ in order to clarify the meaning of that idea. Moreover, he also uses the notion of ‘metastability’ – borrowed from the thermodynamic theory of metastable states – to give to the idea of ‘preindividual’ an original meaning. In this essay, we first seek to understand the problematic relationship between Simondon and the presocratic thought concerning genesis. Then we analyse the groundings of the Simondonian method, which consists in borrowing notions and paradigms from scientific theories dealing specifically with transformation processes and changing systems. The purpose of this examination is to question the validity of a thought process that aims to enrich metaphysical reflexion by means of an analogical method which takes into account the development of scientific theories. We try to show that the simondonian ‘transductive’ method both avoids restraining philosophical thinking to a metaphorical use of scientific thought and falling into a reductionist positivism.